PERBEDAAN PENGARUH TERAPI SINAR INFRA MERAH DAN BACK EXERCISE TERHADAP NYERI PUNGGUNG BAWAH - Prasetyo, Eko Budi (Jurnal Fisioterapi dan Rehabilitasi; Vol 2 No 2 (2018): Jurnal Fisioterapi dan Rehabilitasi, 2018)
The purpose of this study to determine differences in the effect of back exercises to increase flexibility of the spine, the lower back pain and spinal flexibility, and to investigate the interaction between type of therapy , low back pain.Type of research is that the study is a quasi-experimental, with a pretest - posttest design approach . With the method of taking samples is purposive incidental sampling through inspection procedures to establish the diagnosis of lower back pain.The results in this study are reduction in lower back pain and increase spinal flexibility but there is no effect and a significant interaction between the type of physical therapy to increase flexibility and decrease lower back pain , then there is no significant difference between the type of therapy to lower back pain. Based on the conclusions obtained the following results : The type of physical therapy infrared and william flexi exercise compared with other types of physical therapy infrared and Mc . Kenzie exercise.